Principal Leadership in the Development of Professional Learning Communities in Public High Schools Kampar Regency - Yenita, Resi; Andriani, Dwi Esti (FKIP - Universitas Riau, 2025)
School quality improvement increasingly depends on teacher collaboration and continuous professional development, making Professional Learning Communities (PLCs/KBP) a strategic mechanism in strengthening learning culture in schools. This study aims to gain an in-depth understanding of principals’ leadership in developing PLCs at public high schools in Kampar Regency, focusing on principals’ views of PLC urgency, implementation challenges, and leadership practices in planning, managing, and evaluating PLC activities. The research employed a qualitative approach with a basic qualitative design. Informants were selected using maximum variation sampling, involving principals, vice principals, PLC coordinators, and teachers from six public high schools. Data were collected through semi-structured interviews and documentation, then analyzed using thematic analysis through initial coding, categorization, and theme development. Trustworthiness was ensured through source and technique triangulation, member checking, and audit trails. Findings show that principals perceive PLCs as collective learning spaces for sharing good practices and collaboratively solving instructional problems, rather than administrative routines. Key challenges include limited time, perceptions of PLCs as additional burdens, digital competence gaps, inconsistent attendance, and shallow reflection. Principals addressed these through participatory, instructional, and distributive leadership, enabling flexible scheduling, data-based evaluation, structured reflection, and reinforcement. Overall, effective principal leadership strengthens collaborative culture and enhances teacher professionalism.